Direct observation of DME carbonylation in the different channels of H-MOR zeolite by continuous-flow solid-state NMR spectroscopy. Issue 94 (9th October 2015) - He, Ting; Ren, Pengju; Liu, Xianchun; Xu, Shutao; Han, Xiuwen; Bao, Xinhe
Abstract : Surface acetyl intermediates on HMOR zeolites (CH3 CO-Z) were detected during DME carbonylation using in situ continuous-flow 13 C MAS NMR spectroscopy. Abstract : The dynamic evolution of acetyl intermediates in the two different channels of H-mordenite (H-MOR) zeolite during dimethyl ether (DME) carbonylation is tracked by using in situ solid-state NMR spectroscopy under continuous-flow conditions. Thus, the reaction path via methyl acetate produced over active sites in 8 member ring (MR) channels, followed by diffusion into 12 MR channels, is proposed.